Academic productivity in higher education in Mexico: from theory to practice - Gordillo Salazar, Jessica Montserrat (2020)
Productivity is one of the basic concepts of economic sciences, is well-known as a relationship between supplies (inputs) and products (outputs), generally associated with goods-producing organizations. However, the new economy, supported by the tertiary sector has its main strength in those knowledge-based service organizations (SBC) such as education, where productivity becomes more complex to explain. The purpose of this document is to provide an overview of the divergency about the concept of academic productivity in higher education institutions in Mexico, through a theoretical and empirical documentary review. Academic productivity in Mexico is linked to four activities carried out by full-time teachers: teaching, tutoring, academic management and knowledge generation and application, the latter according to the Program for the Professional Development of Teachers in Higher Education. As a result in empirical evidence, not just for Mexico, shows how academic productivity is limited to studying activities related to the generation and application of knowledge, on the other hand, few incorporate teaching and none to tutoring and academic management. The document shows how academic productivity is not conceptually defined, nor normatively; as a result of itan objective assessment between institutions, countries or regions cannot be established.